2009
DOI: 10.1177/0009922809337531
|View full text |Cite
|
Sign up to set email alerts
|

Parent Involvement Is Associated With Early Success in Obesity Treatment

Abstract: Parental involvement may be helpful in identifying who is likely to do well in a weight loss program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 40 publications
2
49
1
Order By: Relevance
“…In the study by Wadden et al 102 of adolescent obesity treatment, greater attendance at treatment sessions by mothers was associated with greater weight loss by adolescents across all treatment groups. Heinberg et al 116 recently reported that parental involvement in treatment, as assessed by the family's case manager on a 4-point Likert scale (from 0ϭnone to 4ϭex-tremely), predicted weight loss among 104 children enrolled in a 12-week intervention. Specifically, children with the lowest parental involvement were less likely to lose any weight or to have clinically significant weight loss (Ն2 kg).…”
Section: Is Greater Parental Adherence To Core Behavior Change Stratementioning
confidence: 99%
“…In the study by Wadden et al 102 of adolescent obesity treatment, greater attendance at treatment sessions by mothers was associated with greater weight loss by adolescents across all treatment groups. Heinberg et al 116 recently reported that parental involvement in treatment, as assessed by the family's case manager on a 4-point Likert scale (from 0ϭnone to 4ϭex-tremely), predicted weight loss among 104 children enrolled in a 12-week intervention. Specifically, children with the lowest parental involvement were less likely to lose any weight or to have clinically significant weight loss (Ն2 kg).…”
Section: Is Greater Parental Adherence To Core Behavior Change Stratementioning
confidence: 99%
“…Whilst these interventions are important and have the potential to play a part in an overarching anti-obesity strategy, children can develop a tendency towards overweight and obesity before they reach school age (Mech, Hooley, Skouteris, & Williams, 2016; Ventura & Birch, 2008), with parental practices in relation to food having an effect on this trajectory (Golan, Weizman, Apter, & Fainaru, 1998; Heinberg et al, 2010; Spruijt-Metz, Lindquist, Birch, Fisher, & Goran, 2002; Ventura & Birch, 2008). However, studies reporting on interventions for treating obesity in children may produce results which cannot be generalized to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Our intervention took place in primary care (level 1) where it should be implemented first for the purposes of preventing the need to get to levels 2 and 3. Furthermore, many of the efforts to prevent overweight and obesity are done in school settings, where it is not possible to work with the families and get them involved in pursuing healthy dietary habits and regular physical exercise [31][32][33] . Thus, another strong point of the Obescat study is that it was done in PC settings.…”
Section: Discussionmentioning
confidence: 99%